Series ISO 9000:2001 Standards NTP - García P, Manuel (2001)
The difference between the number of ISO 9000:1994 Standards NTP and NTP ISO 9000:2001 is the first priority assurance, and the second improvement. in this article is intended to illustrate the major changes and benefits that come with the new version of the series ISO 9000:2001 Standards NTP